Bacterial wilt of Kaempferia galanga L. caused by Pseudomonas solanacearum (Smith) Smith - MANOJ, G N DAKE, P S (Journal of Spices and Aromatic Crops, 1995)
Pseudomonas solanacearum is reported for the first time causing bacterial wilt of Kaempferia (Kaempferia galanga) from Kerala, India.